Impact assessment of water savings technologies for bridging the gap from lab to land - Patel, Neelam; Rajput, T B S; Parihar, S S; Dabas, J P S; Kumar, Mukesh (Indian Farming, 2020)
Significant savings of water (30- 60%), energy (30-40%), and labor (20%) with increase in production (18.2 to 50%) was resulted from technological interventions. Fifteen farmers were encouraged to install biogas plants (2-6 m3 capacity) with a view to use biogas slurry directly to field along with irrigation water to improve water holding and release properties of soils besides substantially reducing the use of water and fertilizer. Biogas technology resulted in reduction of irrigation demand, water and energy requirement for pumping irrigation water to the tune of 5.9, 15.8 and 20% besides 15.2% increase in wheat yield. A low head bucket drip system was designed for kitchen gardening (25 to 50 m2) and 40 family low cost drip systems were installed in the backyards of homes in the selected villages. Bucket kit produced 150 kg of bottle gourd/ 90 kg of bitter gourd/ 75 kg of okra in one season (March to June). Drip systems helped in motivating the farmers to install drip system in regular fields. Consequently, in a span of just two years time, 90 farmers were convinced who adopted drip irrigation in their fields covering about 75 ha area. Increased vegetable production in the villages has generated secondary employment for land less women in picking, sorting and grading of vegetables. The interventions made in the project are of very basic nature and there is a large likelihood of harvesting the similar benefits in terms of water and energy saving and increased yields by implementing the suggested interventions in the entire district.